2022
DOI: 10.1111/mpp.13247
|View full text |Cite
|
Sign up to set email alerts
|

Pexophagy is critical for fungal development, stress response, and virulence in Alternaria alternata

Abstract: Alternaria alternata can resist high levels of reactive oxygen species (ROS). The protective roles of autophagy or autophagy-mediated degradation of peroxisomes (termed pexophagy) against oxidative stress remain unclear. The present study, using transmission electron microscopy and fluorescence microscopy coupled with a GFP-AaAtg8 proteolysis assay and an mCherry tagging assay with peroxisomal targeting tripeptides, demonstrated that hydrogen peroxide (H 2 O 2 ) and nitrogen depletion induced autophagy and pex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…Autophagy is a highly conserved process where proteins, membranes, and organelles are broken down and repurposed to sustain energy balance within eukaryotic cells [39,40]. In this study, the ATG8, a marker to monitor autophagosome formation [36], was characterized in A. flavus. We identified the atg8 gene and found that the ATG8 protein plays a crucial role in various aspects of A. flavus biology, including vegetative growth, conidial development, pathogenicity, resistance to ROS, and AFB1 biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Autophagy is a highly conserved process where proteins, membranes, and organelles are broken down and repurposed to sustain energy balance within eukaryotic cells [39,40]. In this study, the ATG8, a marker to monitor autophagosome formation [36], was characterized in A. flavus. We identified the atg8 gene and found that the ATG8 protein plays a crucial role in various aspects of A. flavus biology, including vegetative growth, conidial development, pathogenicity, resistance to ROS, and AFB1 biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…The abovementioned data indicate the involvement of ATG8 in responding to these stress stimuli in A. flavus. In fungi, autophagy has been recognized as essential for oxidative stress resistance [36]. Therefore, the resistance ability of Δatg8 mutant against oxidative stress was measured.…”
Section: Response Of Atg8 To Multiple Stresses In a Flavusmentioning
confidence: 99%
See 1 more Smart Citation
“…Midbody rings recognize autophagy receptors such as SQSTM1 and NBR1 during selective autophagy [ 26 ]. Pexophagy is the selective destruction of peroxisomes via autophagy; peroxisomes recognize autophagy adaptors autophagy-related 36 (ATG36), ATG40, and peroxisomal biogenesis factor 3 (PEX3), and autophagy receptors SQSTM1 and NBR1 [ 27 ]. Zymophagy selectively degrades damaged or surplus zymogen granules via autophagy; zymogen particles bind to autophagy receptors, including SQSTM1 [ 28 ].…”
Section: Mechanism Of Autophagy Pathwaysmentioning
confidence: 99%
“…The biosynthesis of fungal secondary metabolites is regulated or impacted by a wide variety of proteins, signals, and environmental factors ( 19 , 20 ). Studies in the tangerine pathotype have identified components in the mitogen-activated protein (MAP) kinase pathways, peroxisome complex activities, and autophagy-related processes that are required for ACT biosynthesis and virulence ( 21 24 ). A basal transcription factor II H subunit (tfb5) and a GATA transcription factor (AreA) have also been shown to be required for ACT biosynthesis, sporulation, and virulence in the tangerine pathotype ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%